Atrial Anti-Arrhythmic Effects of Heptanol in Langendorff-Perfused Mouse Hearts - Tse, Gary; Tse, Vivian; Yeo, Jie Ming; Sun, Bing (PLOS ONE, 2016)
Acute effects of heptanol (0.1 to 2 mM) on atrial electrophysiology were explored in Langendorff-perfused mouse hearts. Left atrial bipolar electrogram or monophasic action potential recordings were obtained during right atrial stimulation. Regular pacing at 8 Hz elicited atrial activity in 11 out of 11 hearts without inducing atrial arrhythmias. Programmed electrical stimulation using a S1S2 protocol provoked atrial tachy-arrhythmias in 9 of 17 hearts. In the initially arrhythmic group, 2 mM heptanol exerted anti-arrhythmic effects (Fisher’s exact test, P < 0.05) and increased atrial effective refractory period (ERP) from 26.0 ± 1.9 to 57.1 ± 2.5 ms (ANOVA, P < 0.001) despite increasing activation latency from 18.7 ± 1.1 to 28.9 ± 2.1 ms (P < 0.001) and leaving action potential duration at 90% repolarization (APD90) unaltered (25.6 ± 1.2 vs. 27.2 ± 1.2 ms; P > 0.05), which led to increases in ERP/latency ratio from 1.4 ± 0.1 to 2.1 ± 0.2 and ERP/APD90 ratio from 1.0 ± 0.1 to 2.1 ± 0.2 (P < 0.001). In contrast, in the initially non-arrhythmic group, heptanol did not alter arrhythmogenicity, increased AERP from 47.3 ± 5.3 to 54.5 ± 3.1 ms (P < 0.05) and activation latency from 23.7 ± 2.2 to 31.3 ± 2.5 ms and did not alter APD90 (24.1 ± 1.2 vs. 25.0 ± 2.3 ms; P > 0.05), leaving both AERP/latency ratio (2.1 ± 0.3 vs. 1.9 ± 0.2; P > 0.05) and ERP/APD90 ratio (2.0 ± 0.2 vs. 2.1 ± 0.1; P > 0.05) unaltered. Lower heptanol concentrations (0.1, 0.5 and 1 mM) did not alter arrhythmogenicity or the above parameters. The present findings contrast with known ventricular pro-arrhythmic effects of heptanol associated with decreased ERP/latency ratio, despite increased ERP/APD ratio observed in both the atria and ventricles.